Oom Paul - Brooks, Vincent (Day & Son, 1900)
Scholarly notes may be added at a later date.
Vanity Fair, March 8th 1900
1 print : col.
Keywords: Caricatures; Cartoons; Kruger, Paul, 1825-1904; Pipe smoking; South Africa -- Politics and government -- 1836-1909